DESCRIPTION OF ELDERLY DEPRESSION LEVELS - Livana PH; Yulia Susanti; Lestari Eko Darwanti; Rina Anggraeni (NURSCOPE: Jurnal Penelitian dan Pemikiran Ilmiah Keperawatan, 2018)
Introduction: Increased life expectancy has an impact on the number of elderly people, thus changing health problems and social maps due to a decrease in the productivity of the elderly to organs. Methodology: Research with quantitative methods using descriptive study design. The sample size is 143 elderly. The technique of taking samples using purposive sampling, research has been conducted in the Village "B" Kendal Regency. The instrument used was a questionnaire to identify the characteristics of the elderly, including age, education, gender, marital status, family type, employment, income. Depression levels were measured using a Geriatric Depression Scale (GDS) questionnaire with 30 question items. Data were analyzed using frequency distribution. Results: the majority of the elderly aged 60-74 years, male sex, still have a partner, do not go to school, do not work, no income and type of extended family. The level of Depression in the Elderly is mostly normal as many as 53 people (46.9% ) Discussion: Nurses are expected to provide understanding in the form of counseling or counseling for the elderly and their families, so that further research is expected to identify factors that influence the occurrence of depression in the elderly.